(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A volumetric muscle loss (VML) is the loss of skeletal muscle with associated functional impairment, also known as traumatic or surgical muscle loss. Major muscle tissue loss occurs in personnel on battlefields who have suffered serious injuries. As a result of lost satellite cells, matrix degradation, and persistent upregulation of proinflammatory markers, the muscle cannot regenerate or achieve proper function. So, in the present study, we formulated the azilsartan hydrogel (0.5 and 1%) and further investigated the effect of the azilsartan (AZL) hydrogel in the VML rat model. For that, the volumetric muscle loss was done in the gastrocnemius muscle of 24 rats. The animals were divided into 5 groups: uninjured, VML, VML+ Ethanol, VML+AZL (0.5%) and VML+AZL (1%). The hydrogels were applied daily for 28 days at the injury site. Our results showed that AZL (1%) improved the gastrocnemius weight and their weight-to-length ratio. Also, the oxidative stress and antioxidant levels in skeletal muscle of VML were restored. In conclusion, these results showed that azilsartan hydrogel is effective in volumetric muscle loss induced in rats and could be taken as a therapeutic strategy.